An evaluation of the forest school program in a state preschool in Istanbul - Eroğlu, Sümeyra Büşra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
Using qualitative research techniques, this study was designed to explore the experiences of people who were involved in the implementation of the Forest School program in a state preschool in Istanbul. The preschool included in the study was purposefully selected because I, as a researcher was one of the few Forest school leaders both in Turkey and in that particular school and the school was the only state school in Istanbul with a Forest school program at the time the study was conducted. Throughout the implementation I reflected on my experiences, during the data collection I explored the experiences of the parents and the forest school leaders via interviews and the children’s experiences via field notes and observations. The examination of the program activities with its goals provided a deep understanding of how the case preschool was able to use Forest School practices while still working within the context of a state school curriculum. The results indicated that the teachers’ motivation played a key role in the implementation and maintenance of the Forest School program and that the children’s interests and the parents’ positive perceptions of the program allowed for the program to continue. Although the program lasted for twelve sessions mostly at the school garden, both the observations and the parent reports revealed that forest school program supported each child in different developmental areas. Finally, the study concluded that it is within possibility that the physical settings of state schools can be turned into a setting for outdoor learning.
Keywords: Forest school.; Outdoor recreation for children.; Environmental education.